Modular-based psychotherapy (MoBa) versus cognitive-behavioural therapy (CBT) for patients with depression, comorbidities and a history of childhood maltreatment: study protocol for a randomised controlled feasibility trial - Elsaeßer, Moritz; Herpertz, Sabine; Piosczyk, Hannah; Jenkner, Carolin; Hautzinger, Martin; Schramm, Elisabeth (BMJ open, 2022)
Introduction In depression treatment, most patients do not reach response or remission with current psychotherapeutic approaches. Major reasons for individual non-response are interindividual heterogeneity of etiological mechanisms and pathological forms, and a high rate of comorbid disorders. Personalised treatments targeting comorbidities as well as underlying transdiagnostic mechanisms and factors like early childhood maltreatment may lead to better outcomes. A modular-based psychotherapy (MoBa) approach provides a treatment model of independent and flexible therapy elements within a systematic treatment algorithm to combine and integrate existing evidence-based approaches. By optimally tailoring module selection and application to the specific needs of each patient, MoBa has great potential to improve the currently unsatisfying results of psychotherapy as a bridge between disorder-specific and personalised approaches. - Methods and analysis In a randomised controlled feasibility trial, N=70 outpatients with episodic or persistent major depression, comorbidity and childhood maltreatment are treated in 20 individual sessions with MoBa or standard cognitive-behavioural therapy for depression. The three modules of MoBa focus on deficits associated with early childhood maltreatment: the systems of negative valence, social processes and arousal. According to a specific questionnaire-based treatment algorithm, elements from cognitive behavioural analysis system of psychotherapy, mentalisation-based psychotherapy and/or mindfulness-based cognitive therapy are integrated for a personalised modular procedure.As a proof of concept, this trial will provide evidence for the feasibility and efficacy (post-treatment and 6-month follow-up) of a modular add-on approach for patients with depression, comorbidities and a history of childhood maltreatment. Crucial feasibility aspects include targeted psychopathological mechanisms, selection (treatment algorithm), sequence and application of modules, as well as training and supervision of the study therapists. - Ethics and dissemination This study obtained approval from the independent Ethics Committees of the University of Freiburg and the University of Heidelberg. All findings will be disseminated broadly via peer-reviewed articles in scientific journals and contributions to national and international conferences. - Trial registration number DRKS00022093.